Redescription of Parilia alcocki Wood-Mason, in Wood-Mason & Alcock, 1891 (Decapoda, Brachyura, Leucosiidae) from southeast India - Prema, M.; Ravichandran, S.; Ng, Peter K. L. (Zootaxa, 2018)
Parilia alcocki Wood-Mason, in Wood-Mason & Alcock, 1891, the type species of Parilia Wood-Mason, in Wood-Mason & Alcock, 1891, described from the Bay of Bengal, is one of the largest known leucosioid crabs, reaching carapace widths of over 50 mm. It is, however, not well known and its male gonopods have never been figured. A series of specimens of this species obtained from a fishing port in Tamil Nadu, India, allows for a comprehensive re-description and illustrations of the species. Its distinguishing characters from congeners are discussed.